Analisis Kepatuhan Checksheet CLSR Ground Disturbance pada Pekerjaan Penggalian di PT XYZ - Andi Mutiara Senja (Fakultas Rekayasa dan Teknologi Industri, 2025)
Excavation work is one of the operational activities with a high level of risk, especially in the oil and gas industry which involves underground utilities, pipelines, and cable networks. Potential hazards include underground utility damage, pipeline leakage, and worker injuries. Therefore, effective safety control is required through the implementation of Corporate Life Saving Rules (CLSR). This study aims to analyze the compliance level of CLSR checksheets in excavation work and identify the factors causing non-compliance using the fishbone diagram approach. The research method used field observation, interviews, and documentation during excavation activities at PT XYZ. The instruments used include a supervisor checksheet consisting of 31 safety indicators and a frontliner checksheet consisting of 11 safety indicators. Data analysis was conducted quantitatively by calculating the compliance percentage and qualitatively using a fishbone diagram to identify the root causes of non-compliance. The results show that most indicators have been complied with, however two indicators show the highest non-compliance rate of 75%, namely incomplete use of personal protective equipment (PPE) and poor housekeeping conditions. The fishbone analysis indicates that the causes of non-compliance originate from human factors, work methods, equipment, materials, and environmental conditions. Therefore, increased supervision, PPE awareness programs, and periodic evaluation of CLSR checksheet implementation are required to improve worker compliance with occupational safety standards. Keywords: Occupational safety, CLSR, checksheet, excavation work, fishbone